Assessment Of The Reliability Of The DPRD Building Of East Kalimantan Province - Wibawa, Agus; Tukiman; Mahendra, Wahyu (ARRUS Journal of Engineering and Technology, 2025)
The East Kalimantan Provincial Parliament Building Complex was established 35 years ago. Building D of the East Kalimantan Provincial Parliament was inaugurated by the Governor of East Kalimantan H. Suwarna on January 11, 2004. Building D is more than 21 years old and needs to be re-examined The level of building reliability refers to Government Regulation No. 16 of 2021 which is a derivative regulation of Law Number 28 of 2002 concerning Buildings stating that buildings must be managed administratively and also technically, periodic inspections of the reliability of all or part of the building, components, building materials, and/or infrastructure and facilities within a certain period of time to declare the feasibility of function buildings. This study is to determine the level of building reliability from the aspects of architects, structures, utilities, and fire protection, accessibility, and also building layout and environment in the DPRD Building Complex Area, especially Building D of East Kalimantan Province. Qualitative and Quantitative Methods by conducting visual observations, surveys (measuring, taking samples by means of Non-Destructive Test), Counting, Interviews and Questionnaires as well as Project Documents (As Build Drawing), etc. The data was analyzed using descriptive statistics, laws and regulations and the assessment of reliability score values referring to the Journal of Building Reliability of the Mandiyo Priyo Building, Ibnu Herlambang Wijadmiko 2011. The criteria used to determine the reliability of the building are reliable for a score of 95-100, Less Reliable for a score of 75-<95, Unreliable for a score of <75. The research results in the reliability of Architects of 80% (less reliable), reliability of Structures of 96% (reliable), reliability of Utilities & Fire Protection of 83% (unreliable), reliability of accessibility of 84% (less reliable), reliability of Building and Environment of 100% (reliable). Therefore, from the recapitulation of the reliability assessment of the building D of the East Kalimantan Provincial DPRD, a reliability value of 88% (less reliable).